Comparison of Usefulness of Ketamine and Magnesium Sulfate Nebulizations for Attenuating Postoperative Sore Throat, Hoarseness of Voice, and Cough - Rajan, Sunil (Anesth Essays Res, 2017)
CONTEXT: Postoperative sore throat (POST) is a complication that is unresolved in patients undergoing endotracheal intubation. AIM: To compare the effects of ketamine and magnesium sulfate nebulizations in two strengths, on the incidence and severity of POST, hoarseness, and cough. SETTINGS AND DESIGN: Sixty surgical patients undergoing elective abdominal and lower limb surgeries under combined epidural and general anesthesia were included in this prospective, randomized, double-blinded study. SUBJECTS AND METHODS: Patients in each group were nebulized with the respective study drug 15 min prior to the surgery, i.e., ketamine in Group K, magnesium sulfate 250 mg, and 500 mg in Group M1 and Group M2, respectively, and normal saline as control in Group C. A standardized anesthesia protocol was followed for all patients. After extubation, the patients were asked to grade POST, hoarseness, and cough at 0, 2, 4, 12, and 24 h. STATISTICAL ANALYSIS USED: One-way analysis of variance, Chi-square test, Fisher's exact test, paired t-tests, and Wilcoxon's signed-rank test as applicable. RESULTS: Ketamine and magnesium sulfate 500 mg demonstrated a statistically significant decrease in POST at 0, 2, and 4 h, and postoperative hoarseness at 0 h. There was decrease in the incidence and severity of sore throat, hoarseness, and cough at all periods in the study groups as compared with control. CONCLUSION: Nebulization with ketamine 50 mg and magnesium sulfate 500 mg, 15 min before induction of general anesthesia and intubation, reduce the incidence and severity of POST and hoarseness of voice.